Seed bank dynamics and quality in the seagrass Halophila ovalis along estuarine salinity gradients—a case in the Swan-Canning Estuary - Gu, Ruiting; Statton, John; Rahmawati, Susi; Hovey, Renae; Zhou, Yi; Tang, Jianwu; Yu, Shuo; Kendrick, Gary A. (Frontiers in Marine Science, 2022)
The seed bank of Halophila ovalis is crucial for resilience to disturbance through re-establishment. Understanding seasonal changes in abundance and quality of seeds in natural seed banks is critical for seed-based restoration. We selected an estuary in southwestern Australia and investigated the seasonal changes of seed distribution and viability in H. ovalis seed banks. We also adapted an X-ray viability test used for terrestrial seeds to test the viability of H. ovalis seeds. We then simulated the effect of low salinity on seed viability through a short-term indoor experiment. Seed density was significantly different between sites and seasons (0 to 43590 seeds·m-2), and the highest seed density in the seed banks was found after the reproductive season (May). The proportion of viable seeds in the seed bank was less than 22%, and was not subjected to substantial seasonal variability. The density of seeds in the seed bank decreased in spring, which indicated winter conditions were not prompt seed loss. We also predicted that extreme rainfall events and the resulting extremely low salinity would significantly reduce seed viability, and could decrease in seed germination; limit population recruitment. As it rapidly colonizes marine sediments from seeds, H. ovalis was considered an ideal seagrass for restoration purposes. Our results provide physiological information for H. ovalis seed banks to support seed-based restoration plans. Such understanding would enable accurate predictions about seagrass population resilience to extreme climate events in estuaries, where variable and extremely low salinity may limit seagrass population recovery from seeds through decreasing their viability.